Haiku in English - Henderson, Harold Gould. 4 0 16; 5 (Rutland, Vt. : C. E. Tuttle Co., 1967)
A guide to writing haiku--a Japanese form of poetry--in English, explaining what a Japanese haiku is, what an English haiku is or should be, and what English-speaking poets need to do to write, or teach, haiku in English.
Young Adult;Young Adult
Keywords: 2 -- 0; 6; Haiku, English.;Haiku.; 20; 2